MENJADIKAN PEMILIH PEREMPUAN KOTA SEMARANG YANG CERDAS MEMILIH DALAM PEMILU SERENTAK 2019 - Fitriyah Fitriyah; Puji Astuti; Dewi Erowati; Nunik Retno Herawati; Priyatno Harsasto (Jurnal Pengabdian Vokasi, 2020)
The 2019 general election was the first simultaneous election, besides the voter turnout of Semarang City in the last election did not reach the KPU RI's target of 77.5%. This election socialization program was to increase the quantity and quality of voter turnout. The number of women voters in the City of Semarang is greater than men, so women are the target group. This program chose "Kelompok Arisan PKK RT" (neighborhood group) as the target group. Every neighborhood in Semarang has that group, whose members are housewives, who regularly hold monthly meetings. The program chose purposefully three "Kelompok Arisan PKK RT". The Implementation of the program through collaboration with members of the "Relasi" of KPU of Semarang City. The method used is a lecture, dialogue, and questions and answers. The results stated that the election socialization for the "Kelompok Arisan PKK RT" was able to increase the knowledge of women voters about the general election simultaneously.